Vozes do abissal: um estudo etnográfico dos processos comunicacionais do povo Mendonça Potiguara - Rocha Filho, Francisco José da Silva (2020)
This investigation proposes a study with the Mendonça Potiguara indigenous people, Brazil, focusing beyond the communicative processes in the physical world their relationship with the digital environment. We follow a communicational ethnography of the South which is based on Boaventura Santos theories (2007). We identified communicative practices based on the methodology we performed in the indigenous community. We analyzed how digital tools have been used by that group focusing on their Facebook pages: Santa Terezinha Povo Mendonça Potiguara Indigenous Community and Amarelão em Foco blog. We examined the social networks of indigenous leaders during Brazilian presidential election. Also, we observed Chestnut Festival as a communication process. After an investigative study and based on virtual bios concept (SODRÉ, 2009) we raised a hypothesis that indigenous immersion in virtuality and their adherence to cyberspace implies a new assessment of life. The abyssal theory is described by Santos (2009) as a social invisibility field where suppression forces are acting against the inhabitants of this social space. This is the sociological context where indigenous are inserted. In view of this perspective we aim to unveil how indigenous communicative practices causes fissures in the radical line which according to Santos (2009) divides social reality into two universes.